2020
DOI: 10.1136/rapm-2019-101207
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin–norepinephrine reuptake inhibitors for the prevention of migraine and vestibular migraine: a systematic review and meta-analysis

Abstract: Background and objectivesThe role of serotonin–norepinephrine reuptake inhibitors (SNRIs) in migraine prophylaxis has not been completely established. Current treatments for vestibular migraine (VM) are based on scarce evidence. We aimed to perform an updated review focusing on the efficacy and tolerability of SNRIs for migraine and VM prevention.MethodsWe searched the PubMed, Web of Science, and Cochrane Library databases for relevant studies. The primary outcome was migraine frequency. In the case of VM, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
(47 reference statements)
0
15
0
1
Order By: Relevance
“…Tricyclic antidepressants such as amitriptyline or nortriptyline, or SSRIs and benzodiazepines such as clonazepam have been recommended ( 82 ). SNRI have also been suggested as clinically safe and effective for migraine as well as VM prophylaxis but were considered inferior in response to other drugs ( 83 ).…”
Section: Care Gap 6: Lack Of Appropriate Combination Af Pharmacologic and Nonpharmacologic Measures To Treat Vestibular Migraine As Well mentioning
confidence: 99%
“…Tricyclic antidepressants such as amitriptyline or nortriptyline, or SSRIs and benzodiazepines such as clonazepam have been recommended ( 82 ). SNRI have also been suggested as clinically safe and effective for migraine as well as VM prophylaxis but were considered inferior in response to other drugs ( 83 ).…”
Section: Care Gap 6: Lack Of Appropriate Combination Af Pharmacologic and Nonpharmacologic Measures To Treat Vestibular Migraine As Well mentioning
confidence: 99%
“…A number of studies have shown evidence that the selective serotoninnorepinephrine reuptake inhibitor venlafaxine is beneficial for vestibular migraine. 53 Venlafaxine is also often used to treat anxiety, and it may have efficacy in treating PPPD as well since multiple studies have demonstrated selective serotonin reuptake inhibitors to be an important component of PPPD treatment. [54][55][56] Beta-blockers such as propranolol may also have similar overlapping benefits in treating migraine, anxiety, and possibly even PPPD, though their role in the latter disorder has not yet been studied.…”
Section: Multiple Concurrent Diagnosesmentioning
confidence: 99%
“…Various serum factors such as 5-hydroxytryptamine (5-HT), calcitonin gene-related peptide (CGRP), and Mg 2+ have been found to be associated with VM ( van Dongen et al, 2017 ; Wang et al, 2020 ; Zhang et al, 2020 ). Furthermore, some cytokines, such as interleukin-1β, CCL3, CCL22, and CXCL1, have also been found to be valuable in the diagnosis of VM ( Flook et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%